Jewish Antifascism and the False Promise of Settler Colonialism - Kaiser, Max. author. aut Link
IX, 302 p.
Keywords: ‘Across the diaspora, young progressive Jews look at the institutions that run their communities and ask: How did they become morally corrupt? Max Kaiser answers that question for Australia. But, even more importantly, he excavates a lost anti-fascist past from which a younger Jewish generation can draw inspiration as it battles the resurgent fascism of our age.’ – Peter Beinart, editor-at-large, Jewish Currents ‘Jewish anti-fascism of the 1940s is a missing but important chapter in the history of Jews in Australia, as well as the history of the Left and Australian intellectuals’ attitudes to settler colonialism and Australia’s Indigenous population. Now Max Kaiser has written it in a sympathetic, erudite and readable narrative that brings back to life such colourful figures as the writer Judah Waten, artist Yosl Bergner and activists Norman and Evelyn Rothfield.’ – Sheila Fitzpatrick, Australian Catholic University This book takes a timely look at histories of radical Jewish movements, their modes of Holocaust memorialisation, and their relationships with broader anti-colonial and anti-racist struggles. Its primary focus is Australia, where Jewish antifascism was a major political and cultural force in Jewish communities in the 1940s and early 1950s. This cultural and intellectual history of Jewish antifascism utilises a transnational lens to provide an exploration of a Jewish antifascist ideology that took hold in the middle of the twentieth century across Jewish communities worldwide. It argues that Jewish antifascism offered an alternate path for Jewish politics that was foreclosed by mutually reinforcing ideologies of settler colonialism, both in Palestine and Australia. Max Kaiser lives on the land of the Wurundjeri people of the Kulin nation. He completed his PhD at the University of Melbourne, Australia.